Seorang Pemimpin Yang Besar (Tafsiran 1 Tawarikh 11:1-3) - Frischa Nofrianti; Remita Nian Permata Zendrato (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
In the future, theology students are expected to become good leaders for the church, society and the nation. Researchers study 1 Chronicles 11:1-3 to understand how King David became a great leader. This is a reflection for future theology students on what is meant by a great leader and how to be a good leader before God. Researchers used qualitative methods in completing this paper. Researchers hope that this article is useful for readers and adds insight.